Pengaruh Manajemen Tata Usaha Terhadap Pelayanan Arsip Siswa Di SMA Tahfidzul Qur’an An-Najah Martapura - Tatiah (Universitas Achmad Yani Banjarmasin, 2024)
This research aims to determine administrative management in archival activities, student archive services and the influence of administrative management on student archive services at Tahfidzul Qur'an An-Najah Martapura High School. The research method used in this research is descriptive quantitative with data mining tools in the form of questionnaires, interviews and documentation. In this research, the sample was taken using Simple Random Sampling with a sample of 75 students from class X A, X B, XI A and XI B. The data analysis techniques used are descriptive analysis and simple linear regression. Based on the results of a simple linear regression calculation, the result is Y = 27.737 + 0.344 Student archive services will increase by 0.344. The results of calculating the coefficient of determination show that student archive services are influenced by administrative management by 39% and the other 61% are influenced by other variables. From the results of data analysis using the t test with a significance level of 5%, the value of tcount more than ttable is 6.778 more than 1.992, so that it can be concluded that H0 is rejected and Ha is accepted, which means that there is an influence of administrative management on student archive services at Tah-fidzul Qur'an An-Najah Martapura High School.